2021
DOI: 10.1186/s12889-021-11702-y
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis e prevalence, knowledge, and practice of preventive measures among secondary school adolescents in rural Nigeria: a cross-sectional study

Abstract: Background Currently, there is a paucity of data on the knowledge and practice of preventive measures for Hepatitis E infection in Nigerian populations. This study provided data on the prevalence, knowledge and practices of prevention in an adolescent population from Nigeria. Methods This cross-sectional study was conducted over 3 months among rural Nigerian secondary school adolescents. An interviewer-based questionnaire was used to collect data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Only a few studies have reported HEV awareness and knowledge among different populations. 12 , 22 , 31 , 32 Besides HEV awareness, the findings in this study provided valuable insights into hepatitis awareness levels among the respondents, where 83.5% were aware of the disease. The data also provided a better understanding of the demographic and occupational factors linked to hepatitis awareness among Malaysian food handlers.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Only a few studies have reported HEV awareness and knowledge among different populations. 12 , 22 , 31 , 32 Besides HEV awareness, the findings in this study provided valuable insights into hepatitis awareness levels among the respondents, where 83.5% were aware of the disease. The data also provided a better understanding of the demographic and occupational factors linked to hepatitis awareness among Malaysian food handlers.…”
Section: Discussionmentioning
confidence: 83%
“…Poor awareness among the respondents might be due to the disease being an emerging and is not notable. 22 Despite the biases, the results produced several interesting findings on HEV knowledge. This could be corroborated with our findings that hepatitis awareness contributed significant differences in the scores for the HEV knowledge.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast to European countries, HEV transmission in Africa has traditionally been associated with large outbreaks caused by contaminated water consumption and inadequate sanitation practices ( Bagulo et al, 2018 ; Desai et al, 2022 ). Consequently, individuals in rural areas with deficient sanitation and limited access to safe drinking water are likely at the highest risk of HEV infection ( Mbachu et al, 2021 ; Osundare et al, 2021 ). Among villagers, the prevalence of HEV IgG was 8.7%, which closely resembled the prevalence observed in students (9.0%).…”
Section: Discussionmentioning
confidence: 99%